Myelinated Axons in the Auricular Branch of the Human Vagus Nerve - Safi, Sami Alexander; Ellrich, Jens; Neuhuber, Winfried (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2016)
Transcutaneous stimulation of the auricular branch of the vagus nerve (ABVN) resulted in deactivation of temporal lobe structures, similar to invasive cervical vagus nerve (CVN) stimulation. Presumably, both methods stimulated myelinated afferent beta axons mediating anti-convulsive effects. How numbers of A beta axons in the human ABVN compare to those of the CVN is unknown. The ABVN, CVN, recurrent laryngeal nerve (RLN) and thoracic vagus nerve (TVN) were dissected from embalmed bodies. Numbers and calibers of myelinated axons were analyzed in semithin sections. Myelinated axons in the left and right ABVN averaged to 385 and 363, respectively. Numbers of A beta axons measuring 7 mu m averaged to 64 and 78 on the left and right, respectively. Numbers of A beta axons in CVN were estimated by subtracting myelinated presumed motor axons in RLN from the total count of CVN. This resulted in 280 and 504 A beta axons on the left and right, respectively, concurring well with the thick myelinated axon count of the ipsilateral TVN (255 and 466, respectively). Thus, the ratio of A beta axons in the ABVN and CVN was approximate to 1:5 and 1:6 on the left and right side, respectively. These results indicate that transcutaneous ABVN stimulation might be a promising alternative to invasive CVN stimulation. Anat Rec, 299:1184-1191, 2016. (c) 2016 Wiley Periodicals, Inc.
EVALuna2:184250
Keywords: axon caliber; transcutaneous stimulation; vagal afferents; external ear; man